2021
DOI: 10.3390/healthcare9050490
|View full text |Cite
|
Sign up to set email alerts
|

Refugees’ Opinions about Healthcare Services: A Case of Turkey

Abstract: Background: Migration is one of the most important social events in human history. In recent years, Turkey hosted a high number of asylum seekers and refugees, primarily because of continuing wars and radical social changes in the Middle East. Methods: Using a random sampling method, Syrian refugees aged 18 and over, who can communicate in Turkish, were reached via personal contact and a total of 714 refugees participated in the study voluntarily. Results: Turkey has mounted with some success and to point out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
1
1
1
Order By: Relevance
“…These results disagreed with a descriptive study from turkey [9], which noted that State hospitals were the first 42.4%, followed by social security hospitals (18.5%) and private hospitals (12.0%). Also, the results disagreed with another study from turkey [10], which noted that most cases were reported in state hospitals, followed by private hospitals and university hospitals.…”
Section: Resultscontrasting
confidence: 99%
“…These results disagreed with a descriptive study from turkey [9], which noted that State hospitals were the first 42.4%, followed by social security hospitals (18.5%) and private hospitals (12.0%). Also, the results disagreed with another study from turkey [10], which noted that most cases were reported in state hospitals, followed by private hospitals and university hospitals.…”
Section: Resultscontrasting
confidence: 99%
“…Similarly, in the analysis of refugee healthcare by Kuriki and Ikeda [ 15 ] “trained health personnel” and “health expenditure” are used as input variables. The “number of trained health personnel” is a necessary input when evaluating access to health because health workers are the cornerstone of health systems [ 65 ], while “health expenditure” can result in better healthcare provision and is a good gauge for an assessment of the final consumption of healthcare services [ 66 ]. The output indicator is defined according to the context of the analysis [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bu kapsamda hasta memnuniyeti ve hasta sadakatinin sağlanması, sağlık kurumunun sahip olduğu pazarı koruması, pazar payını genişletmesi, pazardaki fırsatları takip ederek bu fırsatları değerlendirmesi, sağlık kurumunun varlığını devam ettirebilmesi için stratejik bir hedef olarak kabul edilmektedir. 6,7 Diğer kuruluşlarda olduğu gibi, hastanelerde de birden fazla müşteri türü bulunmaktadır (doktorlar, üçüncü taraf ödeyiciler, hastalar, aileler vb.). Bununla birlikte, hastanede sunulan hizmetlerin "son kullanıcısı" olan hastanın memnuniyeti ve sadakati, bu diğer bileşenlerin memnuniyeti ve sadakatinin temelini oluşturmaktadır.…”
Section: Introductionunclassified